Source apportionment of perfluoroalkyl substances in Great Lakes fish. (1st December 2021) - Lin, Yan; Capozzi, Staci L.; Lin, Li; Rodenburg, Lisa A.
Abstract: Due to the complex sources and fate of perfluoroalkyl substance (PFAS), their source apportionment in the environment remains a challenge. A data set of 11 straight-chain PFAS in 139 samples of fish in the Great Lakes was analyzed using positive matrix factorization (PMF) to investigate their primary sources, whose spatial variations were examined against the surrounding environmental factors. PMF analysis produced five fingerprints. Factor 1 (72% of Σ11 PFAS, dominated by PFOS) probably represented emissions from primary sources (such as consumer products) and secondary sources (precursors), and increased in average abundance from west to east across the Great Lakes. Factor 2 (13% of Σ11 PFAS) and factor 3 (7% of Σ11 PFAS), highly loaded with long-chain PFAS and PFNA, respectively, were thought to represent PVDF manufacture or processing in metal plating. They showed higher contributions in sparsely populated Lakes Superior and Huron. Factor 4 (5% of Σ11 PFAS, highly loaded with PFOS and PFHxS) presented hot spots near current and former air force bases, suggesting it was related to aqueous film-forming foams (AFFFs). Factor 5 (4% of Σ11 PFAS) contained primarily PFOS and PFOSA, which may imply metabolism of precursors (PFOSA) to PFOS in vivo. Unexpectedly, the spatial trends of the five sources all showed abnormally low values near the more urbanized Chicago and Milwaukee in Lake Michigan, which may be due to their unique wastewater and stormwater infrastructure or may arise from atmospheric transport of precursors. Our study indicated that PMF was an effective tool to identify sources of PFAS in fish despite absorption, distribution, metabolism, and excretion (ADME) processes which might alter fingerprints in fish relative to their surrounding environment. Graphical abstract: Image 1 Highlights: Eleven PFAS were measured by EPA in 139 fish samples from the Great Lakes. Positive Matrix Factorization identified and quantified five sources from this data. PFOS concentrations increased from west to east, possibly due to formation from precursors. Polymer manufacture and AFFFs were dominated in sparsely populated Lakes Superior and Huron. Abstract : PMF2 resolved five PFAS fingerprints in Great Lakes fish data where PFOS was the dominant compound.